Cortical Thickness in Fetal Alcohol Syndrome and Attention Deficit Disorder - Fernández-Jaén, Alberto; Fernández-Mayoralas, Daniel Martín; Quiñones Tapia, Diana; Calleja-Pérez, Beatriz; García-Segura, Juan Manuel; Arribas, Sonia López; Muñoz Jareño, Nuria (Pediatric neurology, 2011)
Fetal alcohol syndrome represents the classic and most severe manifestation of epigenetic changes induced by exposure to alcohol during pregnancy. Often these patients develop attention deficit hyperactivity disorder. We analyzed cortical thickness in 20 children and adolescents with fetal alcohol syndrome and attention deficit hyperactivity disorder (group 1), in 20 patients without fetal alcohol syndrome (group 2), and in 20 control cases. The first group revealed total cortical thickness significantly superior to those of the other two groups. In per-lobe analyses of cortical thickness, group 1 demonstrated greater cortical thickness in the frontal, occipital, and right temporal and left frontal lobes compared with the second group, and in both temporal lobes and the right frontal lobe compared with the control group. This study demonstrated greater cortical thickness in patients with attention deficit hyperactivity disorder and heavy prenatal exposure to alcohol, probably as an expression of immature or abnormal brain development.